Neighborhood segregation and black entrepreneurship - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2017)
We examine the causal effect of neighborhood segregation on black entrepreneurship. We address neighborhood sorting by analyzing city averages and omitted variable bias by instrumenting for segregation using historical railroad configurations. We find that segregation has a significant positive effect: a 10 percentage point increase in the dissimilarity index decreases the racial gap by about 3.3 percentage points. To minimize the effect of cross-city sorting, we use a narrower sample constructed from outcomes of young adults and find a similar effect. Our findings are importantbecause historically, entrepreneurship has been an avenue out of poverty, and entrepreneurship has been promoted as a way to decrease welfare and unemployment. (C) 2017 Elsevier B.V. All rights reserved.